The ameliorative effects of boron against acrylamide-induced oxidative stress, inflammatory response, and metabolic changes in rats. (August 2018) - Acaroz, Ulas; Ince, Sinan; Arslan-Acaroz, Damla; Gurler, Zeki; Kucukkurt, Ismail; Demirel, Hasan Hüseyin; Arslan, Halil Ozancan; Varol, Nuray; Zhu, Kui
Abstract: Acrylamide (ACR) is a hazardous substance associated with the accumulation of excessive reactive oxygen species and causes oxidative stress. Presence of ACR in foods leads to public health concerns due to its known neurotoxic, genotoxic, and carcinogenic effects. The present study investigated the ameliorative effects of boron (B) against ACR exposed rats. Forty Wistar albino male rats, fed with low-boron diet, were randomly and equally allocated into 5 groups. The control group was orally treated with physiological saline as placebo, the second group was orally given 15 mg/kg ACR. The other groups were orally treated with 15 mg/kg ACR and B at the levels of 5, 10, and 20 mg/kg/day for 60 days, respectively. ACR-treatment significantly increased malondialdehyde levels whereas decreased glutathione levels in rat tissues. Also, ACR-treatment increased the activities of superoxide dismutase and catalase in erythrocytes and tissues. Meanwhile, mRNA expression levels of NFĸB, IFN-γ, IL-1β, and TNF-α in liver and brain of rats were increased under ACR treatment. Additionally, ACR caused a significant decrease in the level of high-density lipoprotein, with increase in the levels of low-density lipoprotein, triglyceride, cholesterol, glucose, urea nitrogen, and creatinine. Lastly, B alleviated histopathological alterations induced by ACR in rat tissues. Highlights: Boron (B) reduces acrylamide (ACR) induced toxicity. B inhibits oxidative stress and restores LPO, GSH, SOD, and CAT in rats. B regenerates ACR-induced histopathological alterations in rat tissues. B attenuates inflammatory response and ameliorates biochemical alterations.